DINAMIKA PENGATURAN TENAGA KERJA ASING DI INDONESIA - Djazuli, Riza Fauziah (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2021)
Abstract The unemployment rate in Indonesia has soared high enough since August 2020 with a total of 9,77 million person, while data on foreign labor recorded in 2020 amounted to 98.902 person. From this data, foreign workers from China rank first, namely 35,781 people or the equivalent of 36.17%. The research purposes are, firstly, to analyze the legal aspects of foreign labor in terms of national responsibility which is closely related to Article 27 verse (2) of the Constitution of 1945; secondly, to analyze the efforts to protect Indonesian employment law in terms of the national responsibility which is closely related to Article 27 verse (2) of the Constitution of 1945. This research used descriptive analytical method with normative juridical approach. Aspects of foreign employment law in terms of national responsibility are seen in the regulation of the control of foreign labor which can only be done in a work relationship for a certain time. Even though this needs to be emphasized regarding legal protection and social welfare insurance like domestic workers. In addition, in terms of supervision of foreign workers, there should be no imbalance in rights and obligations between foreign workers and domestic workers.. Efforts to protect Indonesian labor law in terms of the national responsibility can be seen in the implementation of efforts to educate and train domestic labor in order to improve competency standards that are able to compete with foreign labor. Abstrak Angka pengangguran di Indonesia melonjak cukup tinggi terhitung sejak Agustus 2020 dengan jumlah 9,77 juta orang, sementara data Tenaga Kerja Asing (TKA) pada tahun 2020 tercatat berjumlah 98.902 orang. Berdasarkan data tersebut, TKA yang paling banyak di Indonesia berasal dari Negara China yaitu 35.781 orang atau setara 36,17%. Tujuan penelitian ini adalah, pertama untuk Â menganalisis aspek hukum ketenagakerjaan asing ditinjau dari tanggungjawab negara yang memiliki kaitan erat dengan Pasal 27 ayat (2) Undang-Undang Dasar Tahun 1945; kedua untuk menganalisis upaya perlindungan hukum ketenagakerjaan Indonesia ditinjau dari tanggungjawab negara yang memiliki kaitan erat dengan Pasal 27 ayat (2) Undang-Undang Dasar Tahun 1945. Penelitian ini dilakukan dengan metode deskriptif analitis menggunakan pendekatan yuridis normatif. Aspek hukum ketenagakerjaan asing ditinjau dari tanggungjawab negara dilihat pada pengaturan atas pengendalian TKA yang hanya dapat dilaksanakan dalam hubungan kerja pada waktu tertentu. Malahan perlu ditekankan mengenai perlindungan hukum dan jaminan kesejahteraan sosial layaknya tenaga kerja dalam negeri. Selain itu, dalam hal pengawasan tenaga kerja asing seharusnya tidak ada ketimpangan hak dan kewajiban antara tenaga kerja asing dan tenaga kerja dalam negeri. Upaya perlindungan hukum ketenagakerjaan Indonesia ditinjau dari tanggungjawab negara ini dapat dilihat pada implementasi mengenai upaya mendidik dan melatih tenaga kerja dalam negeri guna meningkatkan standar kompetensi yang mampu bersaing dengan tenaga kerja asing.